2019
DOI: 10.4103/jrms.jrms_1057_18
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of three-point compression ultrasound for the diagnosis of proximal deep-vein thrombosis in emergency department

Abstract: Background:This study aimed to assess the accuracy of three-point compression ultrasonography (3PCUS) performed for the diagnosis of proximal deep-vein thrombosis (DVT) in Emergency Department (ED) compared with the results of duplex US (DUS) (whole-leg compression ultrasound).Materials and Methods:The current prospective cross-sectional study with diagnostic test assessment was conducted on adult patients who were referred to the ED of a general teaching hospital in Shiraz, southern part of Iran (September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In most cohort studies, the majority of focused ultrasound examinations for DVT in patients with suspected acute DVT are negative (56 to 77%) [ 13 15 ]. However, most of these patients had signs or symptoms that led to the clinical suspicion of acute DVT.…”
Section: Introductionmentioning
confidence: 99%
“…In most cohort studies, the majority of focused ultrasound examinations for DVT in patients with suspected acute DVT are negative (56 to 77%) [ 13 15 ]. However, most of these patients had signs or symptoms that led to the clinical suspicion of acute DVT.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we recommend the use of three-point compression ultrasonography by an attending physician in an isolation ward for COVID-19 patients with high D-dimer levels. Mousavi-Roknabadi et al 22 ) reported that three-point compression ultrasonography identified the presence of lower-extremity DVT with an accuracy of 96.4% in comparison with whole-leg compression ultrasound. Moreover, three-point compression ultrasonography showed high specificity regardless of the skill of the clinician performing the investigation.…”
Section: Discussionmentioning
confidence: 99%
“…To exclude DVT an operator must follow a protocol as instructed by the software. This protocol resembles the clinical practice of three-point or two-point examinations 33 35 , which means doing compression ultrasound in two to three regions where the greatest risk of developing thrombosis occurs. For three-point compression protocols, these regions include: (1) the common femoral vein at the level of the inguinal crease (LM0–LM4), (2) the superficial femoral vein superior in the adductor canal (LM5–LM7), and (3) the popliteal vein and its trifurcation in the popliteal fossa (LM8–LM10).…”
Section: Methodsmentioning
confidence: 99%